The work-related well-being of social service workers post COVID-19 pandemic: The psychosocial impact of remote vs in-person work - Venusia COVELLI; Morena TAFFARELLO; Marina Angela VISCO; Francesco CHIRICO; Pietro CRESCENZO; Luca COPPETA; Kavita BATRA; Alessandra MARELLI (Journal of Health and Social Sciences)
Introduction: The COVID-19 emergency and the subsequent restrictive measures forced an internal reorganization of social services, including a remote working model. These changes forced Social Service Workers (SSW) to change their work using new technologies, which might have affected their job satisfaction and general well-being. Therefore, the current research aims to compare the remote working situation during the pandemic with the return to in-person work to evaluate how these two models affected the SSW’s job satisfaction and well-being. Methods: SSW working in social service delivery organizations were recruited to participate in an online semi-structured survey comprising the Job Satisfaction Scale, Psychological General Well-Being Index-S, Work-Related Stress Indicator Tool, Organizational Identification Scale, and Positive and Negative Affect Schedule. The survey tool had several open-ended questions to examine participants’ views about the existing interventions in their workplace and what could be improved and implemented on a permanent basis to enhance their well-being at work. Results: A total of 119 social workers accepted to complete the survey. 77 experienced both in-person and remote working. Comparing working in-person with remote working, the quality of life and satisfaction with one’s health do not change. Whereas the perception of the risk of contracting COVID-19 increases when working in-person (M=3.88) than in remote working (M=1.96; p<.05), and the levels of anxiety increase in remote conditions (M=4.51) if compared to in-person working (M=4.06; p<.05). Job satisfaction about the relationship with the superior is better when working in-person than in remote working (M=4.87 vs 4.61; p<.05) and job satisfaction about the relations between the service and the workers is better when working in-person than in remote working (M=4.87 vs M=4.61; p<.05). Significant differences emerge also from the “in-person vs. remote working” comparison regarding all the dimensions of work-related stress. Discussion: Results lead to useful reflections regarding the management of relations with users and colleagues, the psycho-physical well-being of operators, and, more generally, the quality of the services provided about the mode of service delivery and whether they work in-person vs. remote working.